An Investigation Of The Epstein-Barr Virus Serological Status In The Adult Population - Mladenović, Milica; Knežević, Aleksandra (Medicinski podmladak, 2026)
Introduction: Epstein-Barr virus is an ubiquitous virus from the family Herpesviridae, with seroprevalence ˃90% of world population. Primary infection is asymptomatic or in the form of infectious mononucleosis, depending on the age of patient and immune status. EBV establishes a latent infection in B-lymphocytes with occasional reactivation and because of its oncogenic potential, there is an association with numerous malignancies. Data on the EBV seroprevalence in our population is scarce.Аim: The aim of the study is to investigate the EBV serological status in the adult population by detecting specific antibodies against viral antigens.Material and methods: Serum samples of 58 individuals (age: 30.8±13.7 years; gender: M=41.4%, F=58.6%) were tested with comercial ELISA kits for presence of four antibodies against EBV (anti-VCA-IgM, anti-VCA-IgG, anti-EA-IgG, anti-EBNA-IgG). Based on recommendations from literature, every patient was, depending on serology results, classified in appropriate profile of EBV infection (primary, latent, reactivation).Results: In the 89.5% serum samples, antibodies against EBV were detected, with increasing trend of seropositive patients with age: from 87% seropositive samples in population 18-30 years, to 100% in elderly population. The profile of latent infection was detected in 81% of patients, 3.4% profile of primary infection, 3.4% profile of reactivated infection and 1.7% of unknown profile. There was no significant difference (p˃0.05) between titers of anti-VCA-IgG or anti-EBNA-IgG antibodies in different age groups, nor between genders. The significant difference was not found (p˃0.05) in the number of EBV seropositive samples between genders nor between age groups. Conclusion: Our study showed a high rate of latent EBV infection of 81%, which stipulates high grade of EBV infection in studied population. Differeneces in the seroprevalence among genders weren’t found nor among different age groups. Follow-up investigation of EBV seroprevalence in our population is needed in order to monitor the number of reactivated infections and development of malignancies associated with EBV. Keywords: Epstein-Barr virus; seroprevalence; latency; anti-EBV antibodies
Keywords: Epstein-Barr virus; seroprevalence; latency; anti-EBV antibodies